Design, fabrication and experimental studies of compliant flexure diaphragm for micro pump - Roopa, R; Navin Karanth, P; M. Kulkarni, S (International Journal of Engineering and Technology, 2018)
This study reports the performance of piezo actuated compliant flexure diaphragm for micropump and MEMS application. To achieve the high performance of diaphragm at the low operating voltage compliant flexure diaphragm design is introduced. Very limited work has done on the diaphragms of micropump. Large numbers of mechanical micropumps have used plane diaphragms. The central deflection of diaphragm plays an important role in defining the micropump performance. The flow rate of mechanical type micropump strongly depends on the central deflection of diaphragm. In this paper compliant flexure diaphragms are designed for micropump to achieve higher deflection at lower operating voltage. Finite element analysis of compliant flexure diaphragm with single layer PVDF (Polyvinylidene fluoride) actuator is simulated in COMSOL. Compliant flexure diaphragms with a different number of flexures are analyzed. The central deflection of compliant flexure diaphragms is measured for driving voltages of 90V to 140V in 10 steps. The deflection of the compliant flexure diaphragm mainly depends on flexure width and length, the number of flexures in the diaphragm, PVDF thickness, diaphragm thickness and driving voltage. Use of compliant flexure diaphragm for micropump will reduce the mass and driving voltage of micropump. An attempt is made to compare the results of compliant flexure diaphragms with plane diaphragms. From the experimental results it is noticed that the compliant flexure diaphragm deflection is twice that of the plane diaphragm at same driving voltage. Deflection of three flexure and four flexure compliant diaphragms is 10.5Âµm and 11.5Âµm respectively at 140V.Â Â